Chronic Cerebral Ischaemia Stages I-Ii of the Disease: Immune and Metabolic Disorders: Life Sciences-Medicine - Aleksandrovna, Shulginova Anastasiya; Ekaterina Sergeevna, Litvinova; Olga Nikolaevna, Bushmina; Tarasovich, Dudka Viktor (International Journal of Life Science and Pharma Research, 2022)
Due to the increase in average-expectancy life in most developed countries and the environmental deterioration, there has been an increase in cerebrovascular and neurodegenerative diseases. Hence, this study attempts to analyze the chronic Cerebral Ischaemia Stages I-Ii of the disease, immune and metabolic disorders. To fulfil the study’s aim, seventy-five patients of the neurological department of “Kursk Regional Clinical Hospital” suffering from CCI in presence of hypertension, where 32 patients were with the stage I (1st main group) and 43 - with the stage II (2nd main group) at the age of 50 ± 5 years old are examined. In patients with chronic cerebral ischemia (CCI) stages I and II in presence of hypertension, among the 28 studied parameters of the immune and metabolic status of the blood plasma in addition to the content of the C4 component and the complement factor H inhibitor, 92,9% of the indicators were changed from the values of healthy donors at the start of treatment, in the patients with both stages of the disease 73,1% of these parameters turned out to be the same in magnitude and direction of changes, and 26,9% were identical in direction. The data obtained indicate the presence of immune inflammation, oxidative stress, endothelial dysfunction, and activation of lipid peroxidation in patients with CCI. The performed standard pharmacotherapy did not normalize 61,5% of the studied laboratory immune and metabolic indicators changed prior to the treatment in patients with CCI stage I and 76,9% of those with stage II, which, in its turn, makes necessary the correction of immunometabolic disorders at an early stage of the disease, studies of various combinations of preparations with antioxidant, nootropic, metabolic action in complex pharmacotherapy, and the introduction of immunomodulators into the accepted therapeutic regimens are necessary as well.